Quality of life pada lansia : Bagaimana peran dukungan sosial? - Rusdiyanti, Novi; Pratikto, Herlan; Aristawati, Akta Ririn (Fakultas Psikologi Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract The development of the population in the elderly in Indonesia from year to year is increasing, especially in the Nursing Home of Love Services in the City of Surabaya.In the elderly as they get older, the ability to do physical activity or daily activities will decrease which will have an impact on the Quality Of Life of the elderly, especially in the Nursing Home of Love Services in the City of Surabaya. Social support is the most important thing for the elderly in Pnti Werdha to improve the Quality Of Life in the elderly. Good social support can improve the Quality Of Life in the elderly so that they can enjoy life in their old age. The purpose of this study was to see the relationship between social support and Quality Of Life in the elderly at the Nursing Home of Love Services in the City of Surabaya. This research design uses quantitative methods with product moment analysis techniques. This study was conducted on 62 elderly people at the Love Service Nursing Home in Surabaya City using the total sampling method. The measurements in this study used the Quality Of Life scale adapted by the World Health Organization Quality Of Life (WHOQOL) and the social support scale adapted by Sarafino. The results of this study showed that the correlation coefficient was 0.665 with a significance of 0.000. It can be concluded that social support and Quality Of Life have a positive and significant relationship between social support variables and Quality Of Life variables in the elderly in nursing homes. For further researchers can relate Quality Of Life with other variables, so that research on Quality Of Life is more diverse. Keywords: Quality Of Life, Social Support, Elderly Abstrak Perkembangan populasi pada lansia Di Indonesia dari tahun ke tahun terus meningkat, terutama di Panti Werdha Pelayanan Kasih Di Kota Surabaya.Pada lansia semakin bertambahnya usia maka kemampuan untuk melakukan aktivitas fisik atau kegiatan sehari-hari akan mengalami penurunan yang akan berdampak pada Quality Of Life lansia terutama di Panti Werdha Pelayanan Kasih Di Kota Surabaya. Dukungan sosial merupakan hal yang paling penting bagi lansia di Pnti Werdha untuk meningkatkan Quality Of Life pada lansia. Dukungan sosial yang baik dapat meningkatkan Quality Of Life pada lansia sehingga dapat menikmati hidup dimasa tuanya. Tujuan dari penelitian ini adalah untuk melihat hubungan antara dukungan sosial dan Quality Of Life pada lansia di Panti Werdha Pelayanan Kasih Di Kota Surabaya. Rancangan penelitian ini menggunakan metode kuantitatif dengan teknik analisis product moment. Penelitian ini dilakukan kepada 62 lansia di Panti Werdha Pelayanan Kasih Di Kota Surabaya dengan menggunakan metode total sampling. Pengukuran pada penelitian ini menggunakan skala Quality Of Life yang diadaptasi oleh World Health Organization Quality Of Life (WHOQOL) dan skala dukungan sosial yang diadaptasi oleh Sarafino . Hasil penelitian ini menunjukkan bahwa koefisien korelasi sebesar 0,665 dengan signifikansi 0,000. Bisa disimpulkan bahwa dukungan sosial dan Quality Of Life memiliki hubungan yang positif dan signifikan antara variable dukungan sosial dan variable Quality Of Life pada lansia di Panti Werdha. Bagi peneliti selanjutnya dapat menghubungkan Quality Of Life dengan variabel lain, agar penelitian mengenai Quality Of Life lebih beragam. Kata kunci: Quality Of Life, Dukungan Sosial, Lansia